2022
DOI: 10.3390/life12081205
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in the Diagnosis and Management of Type 2 Diabetes Mellitus in the Era of COVID-19 and Single Cell Multi-Omics Technologies

Abstract: Type 2 diabetes mellitus (T2DM) is one of the world’s leading causes of death and life-threatening conditions. Therefore, we review the complex vicious circle of causes responsible for T2DM and risk factors such as the western diet, obesity, genetic predisposition, environmental factors, and SARS-CoV-2 infection. The prevalence and economic burden of T2DM on societal and healthcare systems are dissected. Recent progress on the diagnosis and clinical management of T2DM, including both non-pharmacological and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 190 publications
0
2
0
Order By: Relevance
“…Goyal, 2023 stated global landscape has witnessed a striking surge in T2DM prevalence across nations of varying income levels over the last three decades, recognizing it a pressing public health challenge. But research by Kupai et al, 2022 suggested the advent of omics technologies herald's transformative era in the prediction and management of Type 2 Diabetes Mellitus (T2DM), offering unprecedented insights into its pathophysiology. Major instrumental technologies genomics, proteomics, metabolomics, and Transcriptomics are identifying predictive biomarkers for T2DM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Goyal, 2023 stated global landscape has witnessed a striking surge in T2DM prevalence across nations of varying income levels over the last three decades, recognizing it a pressing public health challenge. But research by Kupai et al, 2022 suggested the advent of omics technologies herald's transformative era in the prediction and management of Type 2 Diabetes Mellitus (T2DM), offering unprecedented insights into its pathophysiology. Major instrumental technologies genomics, proteomics, metabolomics, and Transcriptomics are identifying predictive biomarkers for T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Major instrumental technologies genomics, proteomics, metabolomics, and Transcriptomics are identifying predictive biomarkers for T2DM. The critical data derived from these omics studies not only facilitate early diagnosis but also enable personalized therapeutic interventions, significantly enhancing patient outcomes (Kupai et al, 2022). Omics technologies in T2DM are important because they intricate molecular and biochemical networks underlying the disease, thereby identifying novel targets for prevention and treatment and they provide holistic approach towards precision medicine to control T2DM symptoms at global level (Kupai et al, 2022).…”
Section: Introductionmentioning
confidence: 99%